صوفیہ کی معاشی سرگرمیاں: تحقیقی جائزہ: Economic Activities of Sofia: A Research Review - Fakhar Zaman; Prof. Dr. Humayun Abbas Shams (International Research Journal of Arabic and Islamic Studies, 2024)
Islam provides a set of moral norms and values about the individual and social economic behaviour. Islam has its own economic system on the basis of Divine Guidance and philosophical views. Sūfīs are the soul and practical representatives of Islamic values. Therefore, the have adapted their theory and practice to a wide variety of social, economic and theological environments. It is considered that poverty is an important spiritual value, while on the other hands we find Sūfīs involved in various activities of social economics like trading etc. The main contribution of Sūfīs to economic thought in Islam is a constant pull against giving too high a value to material wealth. Even though, Sūfīs conceptualised poverty, charity and wealth. Sūfī thinkers argue that asceticism is the first step on the path to seek God, but the seeker should renounce material possessions and even the appetite to acquire material goods under the Divine Principles of economy. The discussion has been premeditated to explore the economic activities of Sūfīs in different era of life. Moreover, it has been discussed that how Sūfīs influenced the social economical behaviours in different times.